Mucinous cystadenoma of the appendix causing chronic intermittent right iliac fossa pain: case report - Serkan Unlu; Reyhan Karagul; Metin Dogan (Medicine Science, 2017)
Mucinous cystadenoma of appendix (MCA) is a rare clinical entity with chronic intermittent right iliac fossa pain in the literature (1). MCA is a rare cystic neoplasm of the appendix characterized by villous adenomatous changes of the appendiceal epithelium associated with distension of the appendiceal lumen with mucin. MCA presentation is right iliac fossa pain, similar to an acute appendicitis; but, about 25% of patients are asymptomatic and diagnosed incidentally on imaging or at the time of surgery(2) [Med-Science 2017; 6(1.000): 131-2]